Antimicrobial, Antibiofilm, and Antioxidant Properties of Boletus edulis and Neoboletus luridiformis Against Multidrug-Resistant ESKAPE Pathogens - Garcia, Juliana; Rodrigues, Francisca; Castro, Flávia; Aires, Alfredo; Marques, Guilhermina; Saavedra, Maria José (Frontiers in Nutrition, 2022)
Multidrug resistant ESKAPE pathogens (Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter bau-mannii, Pseudomonas aeruginosa, and Enterobacter species) has become the most recurrent global cause of skin and soft tissue infec-tions, belonging to the WHO priority pathogens list. Successful therapy remains challenging and entails the assessment of novel and successful antibiotics. In this context, mushrooms are considered a valuable and unique source of natural antimicrobial com-pounds. Therefore, the present study aimed to evaluate the antimicrobial and antibiofilm properties of Boletus edulis and Neobole-tus luridiformis aqueous and methanolic extracts against ESKAPE isolates from clinical wound infections. Disk diffusion and microdilution methods were used to assess the antimicrobial activity. Phytochemical characterization was achieved by analysis of total phenols, ortho-diphenols content, antioxidant activity as well as by HPLC-DAD. HFF-1 cell viability was performed by MTT assay. Aqueous and methanolic extracts of B. edulis and N. luridiformis showed antimicrobial and antibiofilm properties against multidrug-resistant bacteria, although with different efficacy rates. The results showed that there is a convincing relation between the content of phenolic compounds, antioxidant activity, and antimicrobial activity suggesting that the presence of phe-nolic compounds may explain the biological effects. HPLC analysis revealed high levels of protocatechuic acid, homogentisic acid, pyrogallol, gallic acid, p-catechin and dihydroxybenzoic acid in the aqueous extract of B. edulis, explaining the highest antimi-crobial and antibiofilm properties. Importantly, the mushrooms extracts were non-cytotoxic at all tested concentrations. Overall, the tested mushrooms extracts are good candidates to further explore its use in the prevention of wound infection, particularly by multidrug-resistant pathogens.